SONA: a relational methodology to identify structure in networks - Glückler, Johannes; Panitz, Robert; Hammer, Ingmar (Zeitschrift für Wirtschaftsgeographie, 2020)
The study of networks has been characterized by a dualism of methods. Researchers either use interpretive methods to explore the quality of social relations, or quantitative methods to assess the formal structure of network connectivity. However, because relational and structural characteristics of networks are interdependent, we present a method for Situational Organizational Network Analysis to overcome this dualism. In sequencing and integrating qualitative, quantitative and action research techniques, SONA is designed to help unveil authentic understandings of socially meaningful structure in compliance with research ethics. Drawing on a decade of research experience we describe the workings of this integrative method and elaborate on its valued-added compared to single methods. Building on selected applications, we demonstrate how the tailored use of SONA enhances cross-validation, supports original theory-building, and empowers reflexive transformative research.
Gesehen am 03.02.2021